2016
DOI: 10.1097/dad.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Cellular Pseudoglandular Schwannoma

Abstract: Cellular schwannoma and pseudoglandular schwannoma are both previously described rare variants of schwannoma. The authors present an unusual case of a cellular spindle cell neoplasm with prominent gland-like structures, having features of both variants. The nature of this lesion was confirmed by histology and immunohistochemistry, with diffuse and strong S100 and membranous collagen type IV staining. The gland-like structures were lined by S100 + cells and contained proteinaceous, mucicarmine-negative material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The degree of glandular atypia does not appear to correlate with that of the spindle cell population; indeed, the presence of glandular differentiation is not thought to have an impact on MPNST behavior, with prognosis being solely related to the malignant spindle cell component [16,20]. The differential diagnosis of GS includes cytokeratin-positive malignant tumors (such as sarcomatoid carcinoma, carcinosarcoma, and synovial sarcoma, among the others) [1,2,10,20], colonization of an otherwise benign schwannoma by metastatic adenocarcinoma [21], as well as pseudoglandular schwannoma (PGS) and mixed tumor of the soft tissues (MT) [11][12][13][14][15]22]. PGS is an uncommon histologic variant of schwannoma characterized by gland-like structures as well as cystic spaces lined by epithelial-like cells of schwannian derivation [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of glandular atypia does not appear to correlate with that of the spindle cell population; indeed, the presence of glandular differentiation is not thought to have an impact on MPNST behavior, with prognosis being solely related to the malignant spindle cell component [16,20]. The differential diagnosis of GS includes cytokeratin-positive malignant tumors (such as sarcomatoid carcinoma, carcinosarcoma, and synovial sarcoma, among the others) [1,2,10,20], colonization of an otherwise benign schwannoma by metastatic adenocarcinoma [21], as well as pseudoglandular schwannoma (PGS) and mixed tumor of the soft tissues (MT) [11][12][13][14][15]22]. PGS is an uncommon histologic variant of schwannoma characterized by gland-like structures as well as cystic spaces lined by epithelial-like cells of schwannian derivation [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Several histologic subtypes of schwannoma have been described, including ancient, cellular, epithelioid, plexiform, neuroblastoma-like, hybrid, and pseudoglandular variants [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A case of ancient schwannoma exhibiting features consistent with the exceedingly rare glandular variant of benign schwannoma (glandular schwannoma, GS) was recently described [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that schwannomas are frequently stained with CD56 [9,10]. CD56 staining of a pseudoglandular schwannoma has been reported in one case in the literature [11]. However, to our knowledge, cytoplasmic staining with WT1 in pseudoglandular areas has not been previously reported.…”
Section: Discussionmentioning
confidence: 67%
“…It has been demonstrated that the immunoprofile of the gland‐like structures (pseudoglands) in PGS are consistent with Schwann cell origin . The pseudoglandular formation comprises an accumulation of proteinaceous fluid and may be due to a degenerative change within the tumor .…”
Section: Discussionmentioning
confidence: 95%
“…PGS is quite distinct from the somewhat better characterized GS variant. PGSs develop cystic spaces lined by Schwann cells that assume a round or epithelioid appearance and this change may be confused with true epithelial differentiation . Histologically separate from Antoni A and B areas, multiple pseudoglandular cystic spaces are present and scattered throughout the tissue in PGS.…”
Section: Discussionmentioning
confidence: 99%